Аналіз можливостей програмного комплексу GEANT4 для моделювання рентгенівського випромінювання - Озерський, К. Л. (ХНУРЕ, 2025)
The study is dedicated to analyzing the potential use of the GEANT4 soft-ware package for modeling in the field of X-ray radiation dosimetry. Key ap-proaches to integrating GEANT4 with the Python language are examined to sim-plify the modeling process and data processing. An analysis of the main methods of interaction between GEANT4 and Python has been carried out, enabling work with essential GEANT4 classes and methods, such as geometry creation, physical process modeling, simulation execution, and result processing. It has been deter-mined that the combination of GEANT4 with Python significantly expands the possibilities for scientific research, allowing for the effective utilization of GEANT4’s powerful capabilities for physical modeling along with Python’s con-venient tools for data analysis and visualization.
Keywords: аналіз можливостей; програмний комплекс